2017
DOI: 10.2147/ijn.s121299
|View full text |Cite
|
Sign up to set email alerts
|

Protein nanocoatings on synthetic polymeric nanofibrous membranes designed as carriers for skin cells

Abstract: Protein-coated resorbable synthetic polymeric nanofibrous membranes are promising for the fabrication of advanced skin substitutes. We fabricated electrospun polylactic acid and poly(lactide- co -glycolic acid) nanofibrous membranes and coated them with fibrin or collagen I. Fibronectin was attached to a fibrin or collagen nanocoating, in order further to enhance the cell adhesion and spreading. Fibrin regularly formed a coating around individual nanofibers in the membranes, and also for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 60 publications
(76 reference statements)
4
27
0
Order By: Relevance
“…The wet pristine membrane and the membrane with an F1 or F2 nanocoating were tested using the puncture testing protocol, described in detail in our earlier study. 13 Six samples were used for each experimental group. In brief, the samples were placed in a customized holder and were punctured with a spherical cup probe at a constant speed of 0.3 mm/s (stepper motor PD28-3-1021; Trinamic, Hamburg, Germany) while the force was being recorded (1,000 Hz, Force sensor Kistler 9203; Kistler, Winterthur, Switzerland).…”
Section: Membrane Puncture Testingmentioning
confidence: 99%
See 3 more Smart Citations
“…The wet pristine membrane and the membrane with an F1 or F2 nanocoating were tested using the puncture testing protocol, described in detail in our earlier study. 13 Six samples were used for each experimental group. In brief, the samples were placed in a customized holder and were punctured with a spherical cup probe at a constant speed of 0.3 mm/s (stepper motor PD28-3-1021; Trinamic, Hamburg, Germany) while the force was being recorded (1,000 Hz, Force sensor Kistler 9203; Kistler, Winterthur, Switzerland).…”
Section: Membrane Puncture Testingmentioning
confidence: 99%
“…Moreover, the coated nanofibrous membrane showed good mechanical properties for withstanding the traction forces generated by fibroblasts. 12,13 In this study, we prepared electrospun PLA membranes with fibrin nanocoatings of various structures. The first nanocoating only coated each individual membrane fiber.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19] In particular, core-shell nanostructures (with extended nanocoating and hollow nanotube) have found a major application in a wide variety of fields. 20 Numerous publications have demonstrated that they are popular for tailoring compositions and space distributions within nanoproducts. 21,22 Core-shell nanostructures should have great potential to develop materials for colon-specific (or colon-targeted) pulsatile drug-release profiles.…”
Section: Introductionmentioning
confidence: 99%